The Power of One: Engagement as the Key to Highly Effective Clinical Instruction - Dan Pratt; Ric Arseneau (Adult Education Research Conference, 2006)
Twenty-two medical students and forty-one clinical faculty speculated on the results of an unusual study. Their speculations resulted in fourteen factors and six propositions that describe the nature of highly effective clinical teaching.
Keywords: Clinical Teaching; higher education